Cuidados de enfermería en pacientes postquirúrgicos con cáncer de tiroides - Espinoza Llerena, Erika Lizbeth (2025)
Nursing has experienced significant evolution in recent years regarding the care of post-surgical patients with thyroid cancer, implementing a set of specific techniques for recovery. The objective established was to identify nursing care for post-surgical patients with thyroid cancer through a literature review. This review adopted a qualitative, applied, and descriptive research approach, through documentary analysis of scientific articles published in journals indexed in academic databases such as Dialnet, Scielo, Scopus, and university repositories. The findings were presented along with a more significant summary of them in relation to nursing care for post-surgical thyroid cancer patients. It was concluded that the main nursing care for patients in the immediate and intermediate postoperative stages with this condition includes vital sign monitoring, hemorrhage surveillance, pain assessment and management, voice quality, identification of signs of hypocalcemia, and timely fall risk monitoring. In the late postoperative period, care focuses on providing emotional support and education on self-care topics such as nutrition, physical activity, and the use of oral calcium supplements. These care practices help improve the quality of life of thyroid cancer survivors.